Welcome to Precision Medicine Communications! (Precision Medicine Communications, 2021)
Welcome to the inaugural issue of Precision Medicine Communications -a biannual, open access, and peer-reviewed journal aiming to publish high-quality research articles in the field of precision medicine. Precision Medicine Communications accept studies that conduct basic and translational research to investigate the role of genetics and gene-environment interactions that influence human health disorders. The Journal publishes research in all areas of precision medicine. Precision Medicine Communications especially invites studies that are innovative in genomic medicine and add scientific insights that can be translated into improved patient care.It especially considers studies investigating the effects of genetic variability on drug toxicity and efficacy, identification and functional characterization of polymorphisms relevant to the pharmacological action and adverse effects of a drug, integration of new developments in the genome project and proteomics into clinical medicine, pharmacology, and therapeutics, clinical implementation of pharmacogenomics, identification of novel genomic targets for drug development, the economics of genome-guided interventions, clinical implementation of pharmacogenomics, pharmacogenomics in developing countries, companion diagnostics and drug development.The journal provides an integrated forum for all players involved - academic and clinical researchers, pharmaceutical companies, regulatory authorities, healthcare management organizations, patient organizations, and others in the healthcare community. Precision Medicine Communications assists these parties to shape the future of medicine by providing a platform for expert commentary and analysis. In the last two decades, rapid advances in technology have enabled researchers to investigate arcane biological phenomena and ask deeper questions at the cellular, molecular and atomic levels. Several cellular processes involved in health and disease are being unraveled at a rapid pace, high resolution, and with unprecedented details. Authors carrying out investigations leveraging these technologies such as next genome sequencing, CRISPR-Cas9, digital medicine, 3-D printing, bioinformatics, and stem cell technologies, are encouraged to submit their findings to Precision Medicine Communications.An important objective of this journal is to provide a platform to the scientific fraternity, especially to the regional and national academics, where they could get their studies published after a rapid, transparent, and high-quality peer review. All the articles published in Precision Medicine Communications will be freely available to readers immediately after their publication. The open-access policy of our journal is likely to increase the readership of articles and will enhance their visibility and citation potential. Therefore, I invite you to submit your work to Precision Medicine Communications.